Pengaruh Komunikasi Interpersonal, Profesionalisme Guru dan Etika Kerja terhadap Kinerja Guru pada SMA Negeri 7 Banda Aceh - Alyasa, Ariefa; Syamsidar Syamsidar; Zikrillah Zikrillah (Jurnal Sains dan Ilmu Terapan, 2025)
This study aims to examine the influence of Interpersonal Communication, Teacher Professionalism, and Work Ethics on Teacher Performance at SMA Negeri 7 Banda Aceh. The research method used is quantitative with a survey approach, and data were collected through a questionnaire distributed to 66 teachers. Data analysis was performed using multiple linear regression with the assistance of SPSS version 27.0. The results show that, partially, Interpersonal Communication, Teacher Professionalism, and Work Ethics each have a positive and significant impact on Teacher Performance. Additionally, these three variables simultaneously also have a significant influence on Teacher Performance with a coefficient of determination value of 0.674, meaning that 67.4% of the variation in teacher performance can be explained by these independent variables. The implications of this study highlight the importance of developing communication, professionalism, and work ethics simultaneously to improve teacher performance. Recommendations are provided to the school to conduct training and competence development regularly to support the improvement of teacher performance and to create a working environment that fosters optimal performance.